Characteristics Of Genetic Predisposition To The Development Of Juvenile Idiopathic Arthritis In Children. (Texas Journal of Multidisciplinary Studies, 2024)
The article presents clinical laboratory features and prognostic criteria of juvenile rheumatoid arthritis. The clinical characteristics of the disease and the results of laboratory analysis are important in choosing an effective treatment method. Medicinal and surgical treatment of joints is recommended, depending on the severity of the disease, the characteristics of the clinical flow and the results of the functional laboratory analysis.